TC299423, a Novel Agonist for Nicotinic Acetylcholine Receptors - Wall, Teagan R.; Henderson, Brandon J.; Voren, George; Wageman, Charles R.; Deshpande, Purnima; Cohen, Bruce N.; Grady, Sharon R.; Marks, Michael J.; Yohannes, Daniel; Kenny, Paul J.; Bencherif, Merouane; Lester, Henry A. (Frontiers in Pharmacology, 2017)
(E)-5-(Pyrimidin-5-yl)-1,2,3,4,7,8-hexahydroazocine (TC299423) is a novel agonist for nicotinic acetylcholine receptors (nAChRs). We examined its efficacy, affinity, and potency for α6β2* (α6β2-containing), α4β2*, and α3β4* nAChRs, using [125I]-epibatidine binding, whole-cell patch-clamp recordings, and synaptosomal 86Rb+ efflux, [3H]-dopamine release, and [3H]-acetylcholine release. TC299423 displayed an EC50 of 30 - 60 nM for α6β2* nAChRs in patch-clamp recordings and [3H]-dopamine release assays. Its potency for α6β2* in these assays was 2.5-fold greater than that for α4β2*, and much greater than that for α3β4*-mediated [3H]-acetylcholine release. We observed no major off-target binding on 70 diverse molecular targets. TC299423 was bioavailable after intraperitoneal or oral administration. Locomotor assays, measured with gain-of-function mutant α6 (α6L9ʹS) nAChR mice, show that TC299423 elicits α6β2* nAChR-mediated responses at low doses. Conditioned place preference (CPP) assays show that low-dose TC299423 also produces significant reward in α6L9ʹS mice, and modest reward in WT mice, through a mechanism that probably involves α6(non-α4)β2* nAChRs. However, TC299423 did not suppress nicotine self-administration in rats, indicating that it did not block nicotine reinforcement in the dosage range that was tested. In a hot-plate test, TC299423 evoked antinociceptive responses in mice similar to those of nicotine. TC299423 and nicotine similarly inhibited mouse marble burying as a measure of anxiolytic effects. Taken together, our data suggest that TC299423 will be a useful small-molecule agonist for future in vitro and in vivo studies of nAChR function and physiology.